Gastrointestinal Disturbances Associated with the Consumption of Sugar Alcohols with Special Consideration of Xylitol: Scientific Review and Instructions for Dentists and Other Health-Care Professionals - Kauko K. Mäkinen (Hindawi Limited, 2016)
Sugar alcohols (polyols) are used in food manufacturing and in medical tests and examinations. d-Glucitol (sorbitol) and d-mannitol were previously the most common alditols used for these purposes. After the 1960s, xylitol became a common ingredient in noncariogenic confectioneries, oral hygiene products, and diabetic food. Erythritol, a polyol of the tetritol type, can be regarded as the sweetener of the "next generation." The disaccharide polyols maltitol, lactitol, and isomalt have also been used in food manufacturing and in medical tests. Consumption of pentitol- and hexitol-type polyols and disaccharide polyols may cause gastrointestinal disturbances at least in unaccustomed subjects. The occurrence of disturbances depends on consumer properties and on the molecular size and configuration of the polyol molecule. Adaptation may take place as a result of enzyme induction in the intestinal flora. Some of the literature on xylitol has been difficult to access by health-care professionals and will be reviewed here. Research and clinical field experience have found no pathology in polyol-associated osmotic diarrhea-the intestinal mucosa having normal basic structure, except in extreme instances. Xylitol is better tolerated than hexitols or the disaccharide polyols. Erythritol, owing to its smaller molecular weight and configuration that differ from other alditols, normally avoids the gastrointestinal reactions encountered with other polyols. This review will also touch upon the FODMAPs diet concept.